Overview of Anorectal Malformations in Africa - Lawal, Taiwo A. (Frontiers in Surgery, 2019)
Anorectal malformation is one of the most common structural congenital malformations treated by pediatric surgeons globally. The outcome of care is largely dependent on the spectrum, clinical features, associated malformations, expertise of the surgeons and available perioperative facilities. Africa has a large burden of unmet surgical needs in children, and as in other low resource settings, local pediatric surgeons are faced with different and challenging clinical scenarios, hence, adopt various measures to enable children with surgically correctable congenital malformations survive. There are increasing collaborations between local surgeons and experts in other continents, which often involves surgeons travelling to Africa on missions or well-structured partnerships. It is highly beneficial for the physician who is interested in global-surgery to understand the terrain in low resource settings and prepare for possible changes in management plan. This review highlights the epidemiology, clinical presentation, treatment and outcome of care of children with anorectal malformations in Africa and provides options adopted by pediatric surgeons working with limited resources.